Bacterial Alkaloid Biosynthesis: Structural Diversity via a Minimalistic Nonribosomal Peptide Synthetase. Issue 6 (21st June 2018) - Klapper, Martin; Braga, Daniel; Lackner, Gerald; Herbst, Rosa; Stallforth, Pierre
Summary: Chemical and biochemical analyses of one of the most basic nonribosomal peptide synthetases (NRPS) from a Pseudomonas fluorescens strain revealed its striking plasticity. Determination of the potential substrate scope enabled us to anticipate novel secondary metabolites that could subsequently be isolated and tested for their bioactivities. Detailed analyses of the monomodular pyreudione synthetase showed that the biosynthesis of the bacterial pyreudione alkaloids does not require additional biosynthetic enzymes. Heterologous expression of a similar and functional, yet cryptic, NRPS of Pseudomonas entomophila was successful and allowed us to perform a phylogenetic analysis of their thioesterase domains. Graphical Abstract: Highlights: The pyreudione synthetase is a monomodular NRPS that displays striking plasticity Heterologous expression of the pyreudione synthetase was achieved in various hosts A functional pyreudione synthetase homolog was found in Pseudomonas entomophila We performed a phylogenetic analysis of different NRPS thioesterase domains Abstract : Nonribosomal peptides are a diverse class of ecologically and clinically relevant natural products. Here, Klapper et al. study one of the simplest bacterial nonribosomal peptide synthetases of different Pseudomonas strains. A single gene, encoding the monomodular pyreudione synthetase, leads to the production of a variety of bioactive alkaloids.